A Bibliometric Analysis on the Relationship between Mega Events and Regional Development - Alexandra BARBU; Luminița NICOLESCU (Revista de Management Comparat International)
The aim of this paper is to contribute with a bibliometric analysis related to the impacts of complex mega-events on regional development: Olympics, World Cups, and Expos. This analysis is supported by data from the Web of Science Core Collection; keyword co-occurrence, collaborative networks, and thematic clusters will be developed with the use of advanced tools like VOSviewer. This study analyzes 339 publications published from 1994 to 2024 on research trends, influential contributors, and the disciplinary diversity of the field. These results point out the following themes: economic impacts, urban development, governance, sustainability, and tourism, while disparities in benefits and challenges concerning inclusivity and environmental concerns are unraveled. It gives a comprehensive mapping of the scholarly discourse that provides much valuable insight for researchers and policy practitioners who aim to make megaevents serve the goal of equitable and sustainable regional growth.